Typification and adulteration analysis of Brazilian honeys: a systematic review from 2010 to 2020 (Research, Society and Development, 2022)
Honey is the most consumed bee product worldwide, due to its characteristic flavor and the nutritional and therapeutic properties. Brazil is among the largest honey-producing countries, however, due to its high demand, both in the national and international markets, more forms of adulteration have been registered, resulting in economic losses to beekeepers and risks to consumers' health. Thus, this research carried out a systematic review through the CAPES journal portal in order to detect the use of metabolomics analysis based on chromatographic and spectroscopic techniques for typification and detection of fraud and contaminants in honey, over the 2010-2020 years. Of the total articles recovered from the platform (n = 184) using the keywords "honey", "Brazil", "gas chromatography", "liquid chromatography", "nuclear magnetic resonance", and "spectrometry”, 25 studies met the parameters of interest. Chromatographic techniques were mainly used for pesticide detection and spectroscopy for metal detection, while the only NMR-based study found unnatural substances in honey. In addition to the importance of adopting these modern analytical techniques in conjunction with chemometrics, it is necessary to create databases for continuously record the evolution of cases and types of frauds, as already done in other countries, corroborating to jeopardize the occurrence of recursive types of frauds and supporting policy-makers to update the current Brazilian legislation that covers this matter, which dates from 2000.